Brain imaging in catatonia: systematic review and directions for future research. Issue 10 (16th July 2020) - Haroche, Alexandre; Rogers, Jonathan; Plaze, Marion; Gaillard, Raphaël; Williams, Steve CR; Thomas, Pierre; Amad, Ali
Abstract: Background: Catatonia is a frequent, complex and severe identifiable syndrome of motor dysregulation. However, its pathophysiology is poorly understood. Methods: We aimed to provide a systematic review of all brain imaging studies (both structural and functional) in catatonia. Results: We identified 137 case reports and 18 group studies representing 186 individual patients with catatonia. Catatonia is often associated with brain imaging abnormalities (in more than 75% of cases). The majority of the case reports show diffuse lesions of white matter, in a wide range of brain regions. Most of the case reports of functional imaging usually show frontal, temporal, or basal ganglia hypoperfusion. These abnormalities appear to be alleviated after successful treatment of clinical symptoms. Structural brain magnetic resonance imaging studies are very scarce in the catatonia literature, mostly showing diffuse cerebral atrophy. Group studies assessing functional brain imaging after catatonic episodes show that emotional dysregulation is related to the GABAergic system, with hypoactivation of orbitofrontal cortex, hyperactivation of median prefrontal cortex, and dysconnectivity between frontal and motor areas. Conclusion: In catatonia, brain imaging is abnormal in the majority of cases, and abnormalities more frequently diffuse than localised. Brain imaging studies published so far suffer from serious limitations and for now the different models presented in the literature do not explain most of the cases. There is an important need for further studies including a better clinical characterisation of patients with catatonia, functional imaging with concurrent catatonic symptoms and the use of novel brain imaging techniques.